Improvements to the ADM1 based Process Simulation Model: Reaction segregation, parameter estimation and process optimization. Issue 12 (December 2022) - Bechara, Rami
Abstract: Anaerobic digestion is a sustainable organic waste treatment technique with energy recovery via biogas generation. This work presents a novel Aspen Plus ADM1-based flowsheet for this process. Three reactor segments were chosen: stoichiometric for the hydrolysis step, kinetic for acido-aceto-methanogenesis, and equilibrium for hydrogenotrophic methane production. Selected parameters- conversion ratios, kinetic pre-exponent and inhibitor factors- were controlled to best fit model and experimental results. The parity plot fitting had an R 2 = 0.999, a slope of 1.0058 and an intercept of −0.8651. Obtained parameter values stressed the importance of inhibitions, and simulation results showcased the bell-shaped curve for acetic and volatile fatty acid reduction. The model was used for a subsequent sensitivity analysis as well as an optimization runs, leading to a 50% higher methane production ratio. The proposed model presents itself as a significant contribution for optimal anaerobic digestion process design. Graphical abstract: Highlights: A robust process simulation model is constructed to simulate anaerobic digestion. The ADM1 model is the basis for kinetic reactions with associated inhibitions. Reaction parameters are optimized to fit literature and model results. pH, inhibition, and pre-exponential reaction factors differ from literature. Preliminary sensitivity analysis and process optimization are realized. Abstract : Anaerobic digestion; Process modeling; Anaerobic Digestion Model 1; Aspen Plus; Process optimization; Parameter fitting